Indentifying maqasid al-Qur’an : a critical analysis of Rashid Rida’s views - Islam , Tajul; Khan, Israr Ahmad (International Islamic University Malaysia, 2011)
This article examines Muhammad Rashid Rida’s (18651935 C.E.) views of Maqasid al-Qur'an. Rida’s work on this subject is one of a few rear pieces that omprehensively deal with this emerging distinctive concept of understanding the Qur’anic discourse. Thus, it is significant to view Rida’s insight and contribution to this subject. This article presents a critical analysis of the ten main objectives of the Qur’an that he dealt with in his book al-Wahy al-Muhammadi as well as Tafsar al-Manar. This study mainly explores the methodological and logical strength of Rida’s identification of objectives of the Qur’an